Pemanfaatan Diapers Bekas Pakai Menjadi Pot Bunga Upaya Menjaga Keseimbangan Alam Berkelanjutan - Hikamah, Siti Roudlotul; Dudiarti, Diah; Safira, Safira; Handini , Witri; Agus Bahtiyar, Muhammad Rifal; Syaugy, Muhammad; Hariyanto, Hariyanto (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The service aims to reduce plastic waste, especially used diapers, to maintain the balance of the natural ecosystem. Diapers are disposable diapers used by babies, toddlers, and the elderly. Increasing the use of diapers can ease the work of families for those who do not have babysitters or nurses. The impact behind its practicality has a big impact on the environment, namely polluting water and soil, which are basic human needs, so it is necessary to have good diapress processing, because diapress contains plastic, which is difficult to decompose. One of the efforts made to reduce diapers and maintain environmental conditions so that they are not polluted is by managing diaper waste into something useful and valuable, such as flower pots. Flower pots are made using the Asset-Based Community Development (ABCD) method, which consists of discovery (studying), dream (dreaming), design (designing), define (determining goals), and destiny (doing). Utilizing diapers in flower pots can reduce the accumulation of rubbish, thereby preventing the danger of flooding, preserving the natural ecosystem, and beautifying the environment.